In-depth characterization of 1, 4-butanediol diglycidyl ether substituted hyaluronic acid hydrogels. (1st May 2023) - Zhang, Tianji; Zhao, Siran; Chen, Yujuan; Wang, Jiandong; Zhang, Wei; Liu, Jianjian; Kan, Ying; Li, Jin-ping; Guo, Xueping; Li, Hongmei
Abstract: BDDE substituted HA hydrogels remain the most commonly used HA product in the biomedical field. The physical and biochemical properties of the hydrogels are dependent on the degree of modification and substitution patterns/positions, thus, characterizing their fine structure is of great importance for quality assurance. In this study, we developed novel LC-MS methods for accurate determination of MoD as well as in-depth characterization of the linkage network. Fragments resulted from enzymatic depolymerization were resolved by a porous graphitic carbon column followed by online tandem-MS for determining the modification site/residue. With high-resolution separation, two types of previously unknown structures were detected in the cross-linked fragments of 2-B-2 and 4-B-2. Based on the feature of resistance to NaBH4 reduction, these structures contain a GlcNAc residue modified at OH1. This special sugar unit likely derived from reducing end of the native polysaccharide could be a signature to discriminate subtle batch to batch variations. Graphical abstract: Unlabelled Image